The Effects of Teaching Technique and Reading Habit towards Student’s Writing Skill at Junior High School in Serang - Arifiatul Hasanah (English Department - University of Sultan Ageng Tirtayasa, 2017)
The purpose of this research is to know the interactive effects of teaching technique, peer evaluation and reading habit towards student’s writing skill at Junior High School in Serang. In this research, the researcher used KTSP as the curriculum of the eighth grade of Junior High School in Serang. The research methodology is experiment. The writer got the data by giving questionnaire, treatment, and test. According to ANOVA table, teaching technique got Sig. 0.000 < 0.05. It means that hypothesis null (Ho) is denied and hypothesis alternative (H1) is accepted. So, there is a significant effect of teaching technique towards student’s writing skill. And for reading habit result got Sig. 0.000 < 0.05. It means that hypothesis null (Ho) is denied and hypothesis alternative (H1) is accepted. So, there is a significant effect of reading habit towards student’s writing skill. While for the interactive effects of teaching technique and reading habit got Sig. is 0.607 > 0.05, it means that hypothesis null (Ho) is accepted and hypothesis alternative (H1) is denied. So, there are not any significant interactive effects of teaching technique and reading habit towards student’s writing skill.Keywords : Conventional; Peer Evaluation; Reading Habit; and Writing Skill